22 jonge kunstenaars. - Galerie Nouvelles Images, Den Haag (Den Haag : Galerie Nouvelles Images, 1988)
Ankum, Thomas ; Van Baal, Gaby ; Van Der Borgh, Joep ; Cauberg, Rinie ; Grolleman, E. Jan ; Hoogervorst, Michel ; De Jong, Ad ; De Jong, Bo ; Van Der Meijden, Petra ; Overberg, Jacqueline ; Slempkes, Hans ; Scholtes, Carolien ; Schouten, Harold ; tenvers, Marijke ; Van Tellingen, Maurice ; Versloot, Ronald ; Vervoort, Karien ; Vlot, Berdy ; Van Weezel Errens, Yvonne ; Wilmering, Luuk ; Van Workum, Marius ; Zeevalking, Elbertien
22 jonge kunstenaars, Galerie Nouvelles Images, Den Haag, 17 januari - 17 februari 1988
boek